2004
DOI: 10.1007/s00421-004-1104-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strength, endurance and combined training on myosin heavy chain content and fibre-type distribution in humans

Abstract: This study investigated the effect of strength training, endurance training, and combined strength plus endurance training on fibre-type transitions, fibre cross-sectional area (CSA) and MHC isoform content of the vastus lateralis muscle. Forty volunteers (24 males and 16 females) were randomly assigned to one of four groups: control (C), endurance training (E), strength training (S), or concurrent strength and endurance training (SE). The S and E groups each trained three times a week for 12 weeks; the SE gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
65
2
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 52 publications
12
65
2
11
Order By: Relevance
“…However, a comparison between completely different training contents seems to be difficult to realize, since it is impossible and impracticable to match strength and endurance workloads when including a variety of specific training methods. Nevertheless, comparisons between the effects of strength and endurance training loads on contractile properties have been done by a variety of authors (Costill et al, 1976;Putman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, a comparison between completely different training contents seems to be difficult to realize, since it is impossible and impracticable to match strength and endurance workloads when including a variety of specific training methods. Nevertheless, comparisons between the effects of strength and endurance training loads on contractile properties have been done by a variety of authors (Costill et al, 1976;Putman et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, concurrent strength and endurance training has been shown to impair the development of power production compared with strength training alone Kraemer et al 1995). It has also been shown that training strength and endurance concurrently interferes with the development of muscle hypertrophy (Kraemer et al 1995;Putman et al 2004). Bastiaans et al (2001) found that replacing a portion of the endurance training with lightly loaded explosive strength training improved short-term peak power output more than endurance training alone.…”
Section: Paragraph Numbermentioning
confidence: 99%
“…Ainda, um maior sincronismo de fibras musculares, embora não seja sugerido como fator importante para a melhora da força máxima, resulta em um menor tempo de obtenção da força máxima, sendo, portanto, um mecanismo responsável pelo aumento na taxa de produção de força [9][10][11] . Já as adaptações morfológicas ao TF incluem o aumento da área de secção transversa fisiológica (AST) da fibra muscular 17,24 , o que resulta no aumento na AST do músculo 13 , bem como no aumento na espessura muscular 6 e uma modificação entre as isoformas de cadeia pesada de miosina, o que ocorre a partir de uma conversão de fibras do subtipo IIX para o subtipo IIa 17,24 . Modificações na AST da fibra são comumente avaliadas a partir de técnicas histoquímicas realizadas após biópsia muscular 17 , enquanto modificações na AST total do músculo e na espessura muscular são avaliadas a partir de técnicas de imagem como ressonância magnética 23 , tomografia computadorizada 9 ou ultrasonografia 6,13 .…”
Section: Efeitos Na Produção De Força E Potência Muscularunclassified